Architectural shop drawing of timber door Part-2 (RFA-416_Rev B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.